2018
DOI: 10.2147/cia.s173372
|View full text |Cite
|
Sign up to set email alerts
|

Association between echo intensity and attenuation of skeletal muscle in young and older adults: a comparison between ultrasonography and computed tomography

Abstract: BackgroundSkeletal muscle experiences both quantitative and qualitative changes with aging. Echo intensity (EI) of the skeletal muscle obtained by ultrasonography (US) has been considered to reflect muscle quality. This technique is noninvasive, easily accessible, and is relatively inexpensive than that of other imaging techniques such as computed tomography (CT). Previous studies have reported that EI is related to several physical performances. However, few studies have investigated the validity of EI agains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 36 publications
1
55
0
2
Order By: Relevance
“…Quadriceps muscle (rectus femoris and vastus intermedius bellies) was evaluated at 30% (proximal or distal was not described) between the anterior superior iliac spine and the proximal end of the patella, in a supine position, for muscle thickness and echo-intensity [47]; at 50% between the anterior superior iliac spine and the proximal end of the patella, in a supine position, for muscle thickness of both bellies [48,49] and echo-intensity of rectus femoris alone [48]; at 30% (proximal or distal was not described) between the anterior superior iliac spine and the proximal end of the patella, in a supine position, for muscle thickness and echo-intensity [50]; at 50% between the anterior superior iliac spine and the lateral epicondyle of the femur, in a standing position, for echo-intensity [51]; at 50% between the greater trochanter and the knee cleft (left or right was not described), in a supine position with the knees in 10°, for muscle thickness, cross-sectional area and echo-intensity and pennation angle [52]; at 15 cm proximal of the superior border of the patella, in a sitting position, for muscle thickness and echo-intensity [53].…”
Section: Upper Legmentioning
confidence: 99%
“…Quadriceps muscle (rectus femoris and vastus intermedius bellies) was evaluated at 30% (proximal or distal was not described) between the anterior superior iliac spine and the proximal end of the patella, in a supine position, for muscle thickness and echo-intensity [47]; at 50% between the anterior superior iliac spine and the proximal end of the patella, in a supine position, for muscle thickness of both bellies [48,49] and echo-intensity of rectus femoris alone [48]; at 30% (proximal or distal was not described) between the anterior superior iliac spine and the proximal end of the patella, in a supine position, for muscle thickness and echo-intensity [50]; at 50% between the anterior superior iliac spine and the lateral epicondyle of the femur, in a standing position, for echo-intensity [51]; at 50% between the greater trochanter and the knee cleft (left or right was not described), in a supine position with the knees in 10°, for muscle thickness, cross-sectional area and echo-intensity and pennation angle [52]; at 15 cm proximal of the superior border of the patella, in a sitting position, for muscle thickness and echo-intensity [53].…”
Section: Upper Legmentioning
confidence: 99%
“…However, it is not clear what exactly the increase of EI after exercise means (Fujikake et al 2009). In resting state, higher value of EI is related to higher proportion of intramuscular adipose, fibrous, or connective tissues (Pillen et al 2009;Watanabe et al 2018). In animal model, focal edema and inflammation fibers were observed several days after eccentric exercise (Sudo and Kano 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Muscle quality measures derived from CT and sonography have been shown to be significantly different, although related. 28 The CT radiologic density value is primarily affected by the presence of intramuscular fat and water content, 62 whereas EI may also be influenced by the presence of fibrous tissue and other connective tissue. 63 Previous research has suggested that EI may be a more effective indicator of muscle quality than radiologic density.…”
Section: Discussionmentioning
confidence: 99%